2018
DOI: 10.1007/978-3-319-75402-4_48
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Splicing for Activation of Coagulation Factor XIII-A in the Fish Retina After Optic Nerve Injury

Abstract: Factor XIII-A (FXIII-A), which has become known as cellular transglutaminase, plays important roles in mediating cross-linking reactions in various tissues. FXIII-A acts as one of the regeneration molecules in the fish retina and optic nerve after optic nerve injury and becomes activated at the site of injury within a few hours. Previous research has shown that activated FXIII-A induces neurite outgrowth from injured retinal ganglion cells and supports elongation of the regenerating optic nerve. However, the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…When HSF1 -MO was pre-injected and the optic nerve was injured under conditions of suppressed HSF1 expression, numerous apoptotic cells were observed in all nuclear layers and the retinal layered structure was severely disrupted ( Figure S4 ). The long-lasting HSF1 gene expression must induce the gene expression of cell survival factors such as IGF-1, Bcl-2, and p-Akt 1–5 days after ONI [ 10 , 12 , 14 ]. Furthermore, the gene expression of OSK was induced rapidly and at the same time after ONI ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When HSF1 -MO was pre-injected and the optic nerve was injured under conditions of suppressed HSF1 expression, numerous apoptotic cells were observed in all nuclear layers and the retinal layered structure was severely disrupted ( Figure S4 ). The long-lasting HSF1 gene expression must induce the gene expression of cell survival factors such as IGF-1, Bcl-2, and p-Akt 1–5 days after ONI [ 10 , 12 , 14 ]. Furthermore, the gene expression of OSK was induced rapidly and at the same time after ONI ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since the work of Sperry in the 1950s, the fish visual system has been the most popular model of CNS regeneration [ 4 , 5 , 6 , 7 , 8 , 9 ]. For the past 20 years, we have examined the regeneration of fish optic nerves from nerve crush to the recovery of visual function by using modern neurobiological tools such as immunohistochemistry [ 10 , 11 , 12 ], cell and tissue culture systems [ 13 , 14 , 15 ], and three-dimensional image processing systems for behavioral analysis [ 11 , 16 , 17 ]. The obtained results revealed that fish optic nerve regeneration includes (i) an early preparation period at 0–4 days; (ii) a middle neurite outgrowth period at 5–30 days; and (iii) a late synaptic refinement period at 1–4 months after optic nerve injury (ONI).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation